STRATEGIES USED BY STUDENTS TO REDUCE ANXIETY IN SPEAKING ENGLISH - Arin Nuraeni; Rara Jingga Bunga Aryatie; Nur Azizah; Silih Warni (ELLTER Journal, 2023)
Speaking English as a foreign language is a complex process that involves not only speaking skills but also various psychological aspects. Students’ anxiety in speaking English as a foreign language has been a prominent area of concern since many English as a foreign language student have been suffering from this feeling and dealing with various strategies to cope with it. This study aimed to investigate the strategies students used to deal with speaking anxiety. The research was conducted in a junior high school in East Jakarta. A total of 100 respondents were selected based on the criteria, which were students who felt anxious about speaking English. The method used in this study is descriptive qualitative. The instruments applied in this study were interviews and Likert scale questionnaires. The data obtained were then accumulated and narrated. The findings indicate that students do not only use one strategy. The highest strategy used by students was Preparation Strategy (69%). Meanwhile, the least strategy (30%), is the Positive Thinking strategy.